Design and fabrication of a vacuum cobweb cleaner (2009)
A visit to high rise buildings will show infestations with cobwebs at the walls and ceilings. These buildings could not be cleaned except through the use of scaffolds and long poles with wet cloth or foam rubber attached to the end. The aim of this research is to design a device to do such cleaning efficiently without the inherent dangers in the use of scaffolding. The design of the vacuum cobweb cleaner was based on parameters used in the design of components such as the vacuum cleaner, floor polishers, and floor scrubbers. After the engineering drawing, materials were selected to strike a balance between the cost and quality. The fabrication of the vacuum cobweb cleaner was mainly through the use of basic manufacturing processes such as cutting, joining, machining and drilling. The performance of the vacuum cobweb cleaner was satisfactory. There is need however to improve the suction of sticky webs.